Impaired Collateral Vessel Formation in Sickle Cell Disease. Issue 5 (May 2018) - Okwan-Duodu, Derick; Hansen, Laura; Joseph, Giji; Lyle, Alicia N.; Weiss, Daiana; Archer, David R.; Taylor, W. Robert
Abstract : Objective—: The adaptive response to vascular injury is the formation of functional collateral vessels to maintain organ integrity. Many of the clinical complications associated with sickle cell disease can be attributed to repeated bouts of vascular insufficiency, yet the detailed mechanisms of collateral vessel formation after injury are largely unknown in sickle cell disease. Here, we characterize postischemic neovascularization in sickle cell disease and the role of neutrophils in the production of reactive oxygen species. Approach and Results—: We induced hindlimb ischemia by ligation of the femoral artery in Townes SS (sickle cell) mice compared with AA (wild type) mice. Perfusion recovery, ascertained using LASER (light amplification by stimulated emission of radiation) Doppler perfusion imaging, showed significant diminution in collateral vessel formation in SS mice after hindlimb ischemia (76±13% AA versus 34±10% in SS by day 28; P <0.001; n=10 per group). The incidence of amputation (25% versus 5%) and foot necrosis (80% versus 15%) after hindlimb ischemia was significantly increased in the SS mice. Motor function recovery evaluation by the running wheel assay was also impaired in SS mice (36% versus 97% at 28 days post-hindlimb ischemia; P <0.001). This phenotype was associated with persistent and excessive production of reactive oxygen species by neutrophils. Importantly, neutrophil depletion or treatment with the antioxidant N-acetylcysteine reduced oxidative stress and improved functional collateral formation in the SS mice. Conclusions—: Our data suggest dysfunctional collateral vessel formation in SS mice after vascular injury and provide a mechanistic basis for the multiple vascular complications of sickle cell disease. Abstract : Supplemental Digital Content is available in the text.